The Republic of Armenia: on the Way to the Information Society - Mikhail A. Vus; Lyudmila V. Chelnokovа; Rafael M. Yusupov (Евразийская интеграция: экономика, право, политика)
The article is devoted to the issues of promotion of the Republic of Armenia on the way of building information society. The national legislation in the sphere of information freedoms and electronic communications is characterized, the peculiarities of legal regulation and administration, management of the national segment of the Internet are discussed.